Relationship between Self-Actualization and Self-Reported Loneliness - Moore, Joseph A.; Sermat, Velio (Canadian Journal of Counselling and Psychotherapy, 2012)
Undergraduate students who wished to enter sensitivity groups filled in Shostrom's Personal Orientation Inventory and also indicated their degree of loneliness. Ss low in loneliness obtained higher scores on the personality scale, with eight of the 12 subscales significantly different from Ss high in loneliness. There follows a discussion on the supported general hypothesis, that individuals who identify themselves as being more lonely are also likely to be less self-actualized.